Proceedings of the 12th ACM SIGMETRICS/PERFORMANCE Joint International Conference on Measurement and Modeling of Computer Syste 2012
DOI: 10.1145/2254756.2254766
|View full text |Cite
|
Sign up to set email alerts
|

Workload analysis of a large-scale key-value store

Abstract: Key-value stores are a vital component in many scale-out enterprises, including social networks, online retail, and risk analysis. Accordingly, they are receiving increased attention from the research community in an effort to improve their performance, scalability, reliability, cost, and power consumption. To be effective, such efforts require a detailed understanding of realistic key-value workloads. And yet little is known about these workloads outside of the companies that operate them. This paper aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
401
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 623 publications
(424 citation statements)
references
References 20 publications
15
401
0
2
Order By: Relevance
“…Characterization of stored data in Facebook servers, which is organized as a key-value store, revealed that both keys and values tend to have modal distributions [42]. File sizes also tend to be modal.…”
Section: Modal Distributionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characterization of stored data in Facebook servers, which is organized as a key-value store, revealed that both keys and values tend to have modal distributions [42]. File sizes also tend to be modal.…”
Section: Modal Distributionsmentioning
confidence: 99%
“…• Accesses to the records of a database display locality, as do accesses to a key-value store, which may be regarded as a simple case of a database [42].…”
Section: Spatial and Temporal Localitymentioning
confidence: 99%
See 3 more Smart Citations